A Feedback Investigation of Comparing Teacher and Students’ Preferences on Writing Conference in a Novice EFL Writing Class - Fitriani, Naria; Sabarniati, Sabarniati (Jurnal Ilmiah Peuradeun, 2019)
To enrich students writing aptitude, it is significant to identify the effective feedback process in the language classroom. While the teacher is presenting the appropriate feedback strategies, it is needed to find whether the students prefer what their teacher applied in order to solve their writing problems. The teacher carried out both written and oral (writing conference) in giving feedback, however, this study aims at comparing the teacher and students’ preferences on the teacher feedback practice qualitatively. The students’ writing assignment of 200 words was submitted before the conference schedule. Receiving the written feedback on their writing sheets, the students read and review their teacher feedback. Next, participating in this study, the students were required to contribute on the questionnaire about their preferences during the conference, while the teacher was interviewed. The results show that the students (58%) in the novice writing class preferred on the writing conference. There were 79% students in English writing program would rather work in personal with their teacher which means each of students work one-to-one. Meanwhile, the teacher preferred providing the written feedback, though she realized that the conference might work better on the novice level.